Human Salivary Histatin-1 Promotes Osteogenic Cell Spreading on Both Bio-Inert Substrates and Titanium SLA Surfaces - Sun, Wei; Ma, Dandan; Bolscher, Jan G. M.; Nazmi, Kamran; Veerman, Enno C. I.; Bikker, Floris J.; Sun, Ping; Lin, Haiyan; Wu, Gang (Frontiers in Bioengineering and Biotechnology, 2020)
Promoting cell spreading is crucial to enhance bone healing and implant osteointegration. In this study, we investigated the stimulatory effect of human salivary histatin-1 (Hst-1) on the spreading of osteogenic cells in vitro as well as the potential signaling pathways involved. Osteogenic cells were seeded on bio-inert glass slides with or without the presence of Hst1 in dose-dependent or time-course assays. 1 scrambled and 6 truncated Hst1 variants were also evaluated. Cell spreading was analyzed using a well-established point-counting method. Fluorescent microscopy was adopted to examine the cellular uptake of fluorescently labelled Hst1 (F-Hst1) and also the cell spreading on sandblasted and acid etched titanium surfaces. Signaling inhibitors, such as U0126, SB203580 and pertussis toxin (PTx) were used to identify the potential role of extracellular-signal-regulated kinase, p38 and G protein-coupled receptor pathways, respectively. After 60 min incubation, Hst1 significantly promoted the spreading of osteogenic cells with an optimal concentration of 10 μM, while truncated and scrambled Hst1 did not. F-Hst1 was taken up and localized in the vicinity of the nuclei. U0126 and SB2030580, but not PTx, inhibited the effect of Hst1. 10 μM Hst1 significantly promoted the spreading of osteogenic cells on both bio-inert substrates and titanium SLA surfaces, which involved ERK and p38 signaling. Human salivary histatin-1 might be a promising peptide to enhance bone healing and implant osteointegration in clinic.